LABOR MARKET DEVELOPMENT IN THE REPUBLIC OF UZBEKISTAN - Razikova Gulmira Sharifovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article analyses of the characteristics and trends of the effective development of the labor market infrastructure, identifies socio-economic problems related to the improvement of its formation efficiency, and researches the main directions of the state and non-state employment services.